Strategi Inovasi Pariwisata Indonesia Untuk Bertahan Pada Masa Pandemi Covid 19 - Andre Wiratha; Nur Kemalasari (PT FORMOSA CENDEKIA GLOBAL, 2022)
The COVID-19 pandemic has changed various aspects of life, including the economic sector such as tourism. At the same time, an innovation strategy is needed so that tourism can survive in the midst of the Covid-19 pandemic. This study aims to introduce applicable strategies that are the key to the revival of tourism in Indonesia. This study uses a descriptive qualitative approach, using a literature study. The results of this study explain how the tourism sector, such as: 1. The travel agency uses one of its strategies in dealing with the pandemic, namely the Virtual Experience where this strategy is an expert trying to teach the audience how to make or do something, make coffee, and learn make-up for example; 2. Tourist Attractions also use the Virtual Music Concert strategy for music lovers who still want to hear their idols sing live during the pandemic even though they are not in the same location as their idols; 3. MICE (Meeting, Incentive, Convention, Exhibition) even implements the Online Exhibition Matters strategy where art lovers can still enjoy indigenous artworks online; 4. Hospitality implements one strategy, namely Work From Hotel specifically for workers who must continue to complete work during the pandemic and hotels provide a comfortable place for workers with complete facilities; 5. Tourism transportation is a public space that can become the center of the spread of the pandemic, therefore each tourist transportation must implement a strategy such as the Chse Protocol In Public Transportation, where transportation must serve passengers who want to travel by paying attention to health protocols (obligation to wash hands, wear masks and maintain distance), in addition, hand sanitizers are placed at each point, checking body temperature, filling e-HAC and many other protocols. and 6. The restaurant also implements the Dine-In Loyalist, Experience Seeker strategy where each restaurant customer is separated by a transparent barrier so that they can still enjoy food but also communicate.